Phytochemical investigation and biological activities of Echium arenarium (Guss) extracts. (May 2018) - Kefi, Sarra; Essid, Rym; Mkadmini, Khawla; Kefi, Asma; Mahjoub Haddada, Faouzia; Tabbene, Olfa; Limam, Ferid
Abstract: The present work was developed to evaluate the in vitro antioxidant, antibacterial, antileishmanial and cytotoxic activities of Echium arenarium (Guss) extracts, and to analyze their phytochemical composition. The highest content of total phenolic compounds was obtained in the ethyl acetate extract which showed the best DPPH scavenging activity and β-carotene bleaching inhibition (IC50 = 1.1 and 9.94 μg/mL respectively). It also exhibited the highest antibacterial activity against Gram-positive bacteria ( L. monocytogenes ; S. aureus ; MRSA, E. faecalis and B. cereus ) and antileishmanial activity against L. major (IC50 = 13.91 ± 0.43 μg/mL) and L. infantum (IC50 = 9.91 ± 0.15 μg/mL). Moreover, the active extract exhibited potent antiamastigote activity (IC50 = 22.48 ± 0.14 μg/mL and 18.59 ± 0.09 μg/mL against L. major and L. infantum respectively). Cytotoxicity studies revealed low toxicity against Raw 264.7 macrophage cell line (IC50 = 145.80 ± 0.84 μg/mL, SI < 10). Luteolin-7-O-glucoside was identified as the major flavonoid component by RP-HPLC analysis. In conclusion, Echium arenarium (Guss) extract was characterized by a wide range of biological activities and could be used as a potential natural anti-infectious drug. Highlights: Several Echium arenarium fractions showed important biological activities. Ethyl acetate fractions showed the highest antioxidant potential. Ethyl acetate displayed the stronger antibacterial and antileishmanial activities. Good selectivity index and specificity for amastigote and promastigote forms. Activity was attributed to the high content of flavonoid and especially to the luteolin-7-O-glucoside.